Evaluation of Executive Education Programs to Enhance Mid-Career Employees Role-based Performance: Organizational Perspective - Kitchlew, Naveda; Shahzad, Khuram; Bajwa, Sami; Aslam, Haris (Journal of Quantitative Methods, 2021)
The main objective of this study is to evaluate the effectiveness of the Executive MBA (EMBA) program from an employers’ perspective in Pakistan. The study adopts a role-based performance lens to evaluate the extent to which an EMBA program has met the sponsoring organizations’ expectations in terms of enhancing the role-based performance of their mid-career employees. Data was collected, through a structured self-administered questionnaire, from 140 EMBA graduates linked to 99 sponsoring organizations in Pakistan. The findings indicate that employers consider job-related tasks the most important aspect of employee performance, followed by teamwork, career development, innovation, and extra role behaviours such as citizenship. Overall, employers are satisfied with the post-EMBA role-based performance of their graduate employees. However, there exists a negative gap between what employers expect from the EMBA program and what these programs deliver in terms of enhancing role-based performance of mid-career employees.